Neurovascular Coupling During Visual Stimulation in Multiple Sclerosis: A MEG-fMRI Study. (1st April 2019) - Stickland, Rachael; Allen, Marek; Magazzini, Lorenzo; Singh, Krish D.; Wise, Richard G.; Tomassini, Valentina
Highlights: A reduced electrophysiological response to a visual stimulus in MS, characterized by reduced gamma power (30–80 Hz), with MEG. A reduced hemodynamic response to a visual stimulus in MS, characterized by reduced BOLD and CBF responses, with fMRI. The coupling between gamma power and BOLD/CBF was not significantly impaired in the MS group. Abstract: The process of neurovascular coupling ensures that increases in neuronal activity are fed by increases in cerebral blood flow. Evidence suggests that neurovascular coupling may be impaired in Multiple Sclerosis (MS) due to a combination of brain hypoperfusion, altered cerebrovascular reactivity and oxygen metabolism, and altered levels of vasoactive compounds. Here, we tested the hypothesis that neurovascular coupling is impaired in MS. We characterized neurovascular coupling as the relationship between changes in neuronal oscillatory power within the gamma frequency band (30–80 Hz), as measured by magnetoencephalography (MEG), and associated hemodynamic changes (blood oxygenation level dependent, BOLD, and cerebral blood flow, CBF) as measured by functional MRI. We characterized these responses in the visual cortex in 13 MS patients and in 10 matched healthy controls using a reversing checkerboard stimulus at five visual contrasts. There were no significant group differences in visual acuity, P100 latencies, occipital gray matter (GM) volumes and baseline CBF. However, in the MS patients we found a significant reduction in peak gamma power, BOLD and CBF responses. There were no significant differences in neurovascular coupling between groups, in the visual cortex. Our results suggest that neuronal and vascular responses are altered in MS. Gamma power reduction could be an indicator of GM dysfunction, possibly mediated by GABAergic changes. Altered hemodynamic responses confirm previous reports of a vascular dysfunction in MS. Despite altered neuronal and vascular responses, neurovascular coupling appears to be preserved in MS, at least within the range of damage and disability studied here.